"My Church Teaches Homosexuality is a Sin" Religious Teachings, Personal Religious Beliefs, and MSW Students' Attitudes toward Sexual Minorities. Issue 2 (3rd April 2021) - Woodford, Michael R.; Atteberry-Ash, Brittanie; Jaffee, Kim; Dessel, Adrienne B.
ABSTRACT: Religious social work students often report less-affirming LGB attitudes, which is often attributed to anti-LGB religious teachings. Yet research often overlooks one's beliefs about their denomination's LGB teachings. We examine the association between MSW students' LGB attitudes, syncretism between religious teachings that "homosexuality is a sin" and students' beliefs about these teachings, and the influence of religiosity on syncretism. Results suggest that personal views about one's denomination's teachings matter, representing a point for educational intervention. Findings highlight the importance of creating opportunities for students belonging to anti-LGB denominations to reflect critically on religious teachings as part of their education.